Exchange Protein Directly Activated by cAMP 2 Enhances Respiratory Syncytial Virus-Induced Pulmonary Disease in Mice - Ren, Junping; Wu, Wenzhe; Zhang, Ke; Choi, Eun-Jin; Wang, Pingyuan; Ivanciuc, Teodora; Peniche, Alex; Qian, Youwen; Garofalo, Roberto P.; Zhou, Jia; Bao, Xiaoyong (Frontiers in Immunology, 2021)
Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infection in young children. It is also a significant contributor to upper respiratory tract infections, therefore, a major cause for visits to the pediatrician. High morbidity and mortality are associated with high-risk populations including premature infants, the eldely, and the immunocompromised. However, no effective and specific treatment is available. Recently, we discovered that an exchange protein directly activated by cyclic AMP 2 (EPAC2) can serve as a potential therapeutic target for RSV. In both lower and upper epithelial cells, EPAC2 promotes RSV replication and proinflammatory cytokine/chemokine induction. However, the overall role of EPAC2 in the pulmonary responses to RSV has not been investigated. Herein, we found that EPAC2-deficient mice (KO) or mice treated with an EPAC2-specific inhibitor showed a significant decrease in body weight loss, airway hyperresponsiveness, and pulmonary inflammation, compared with wild-type (WT) or vehicle-treated mice. Overall, this study demonstrates the critical contribution of the EPAC2-mediated pathway to airway diseases in experimental RSV infection, suggesting the possibility to target EPAC2 as a promising treatment modality for RSV.